Practicing critical oral history : connecting school and community - Lemley, Christine K. (Practicing oral history series, 2018)
Critical oral history: engaging critical inquiry, community-based accountability, and transformative justice -- Reflexivity: practicing self-reflection to sensitively engage people, place, and community -- Relationality: building relationships with people, place, and community -- Responsibility: practicing care for people, place, and community -- Respect: honoring processes and practices to gather stories from people, place, and community -- Reciprocity: giving back to people, place, and community -- Call to action: writing and righting history for people, place, and community